A Unique Story of a Marvellous Career: Life of Hon. Phineas T. Barnum - Benton, Joel, 1832-1911 (Salt Lake City, UT : Project Gutenberg, 1998)
"A Unique Story of a Marvellous Career: Life of Hon. Phineas T. Barnum" by Joel Benton is a historical account likely written in the late 19th century. The book chronicles the life and career of Phineas Taylor Barnum, who is famously known as a showman and one of the founders of modern circus entertainment. It details his humble beginnings, his rise to fame, and the rich tapestry of experiences that shaped his vision for entertainment and business. At the start of the biography, we learn about Barnum's childhood in Bethel, Connecticut, where he was born into a modest family on July 5, 1810. The narrative focuses on his early experiences, including his adventures and misadventures in farming and trade, as well as his first journeys to New York City, where he encountered the complexities of urban life. The beginning emphasizes his innate entrepreneurial spirit, which he demonstrated through various childhood ventures. Barnum's introduction to the world of business sets the stage for his later success as a celebrated showman who embraced both humor and strategy in his performances. (This is an automatically generated summary.)
Release date is 1998-12-01
Scanned by Charles Keller with OmniPage Professional OCR
Keywords: Barnum, P. T. (Phineas Taylor), 1810-1891; Circus owners -- United States -- Biography; Barnum's American Museum